Association between Birth Weight of the Babies and Mode of Delivery: A Cross-Sectional Study - Islam, Shapla; Kabir, Bipasha; Parveen, Shahajadi Shanjida (Bangladesh Armed Forces Medical Journal, 2024)
Background: Birth weight has significant short and long-term effects on health and survival and is a useful predictor of prenatal and postnatal development. Birth weight is likely to play a key role for the infant’s survival because it is one of the strongest predictors of infant mortality risk. The aim of the study was to find out the association between birth weight and mode of delivery. Methods: This was a cross-sectional study conducted at Combined Military Hospital, Ghatail from 15 March 2019 to 30 June 2019. Secondary data were used, which were collected from hospital register during the period of 01 January 2018 to 31 December 2018. The study population was all the newborn babies delivered in CMH, Ghatail during that period and mothers of the newborn babies were respondents of the study. Results: Out of 526 respondents majority (64.83%) were in the age group of 23-32 years with mean age 25.14(range: 18-40) years. Of the newborn babies around half (48.3%) were male. The mean birth weight was 2.92 kg with minimum weight 1.2 kg and maximum 4.2 kg. The data showed that the prevalence of Low Birth Weight (LBW) 13.1%. Majority (84.6%) of the mothers didn’t have any comorbidity, few (15.4%) suffered from comorbidity. 53.8% babies were born by caesarean section (CS) and 46.2% were delivered by normal vaginal delivery. Among the low birth weight babies 65.2% were born by CS. Statistically significant association was found between birth weight of the babies and mode of delivery (p<0.05). Conclusion: Caesarean section cannot be routinely recommended, unless there are other obstetric indications. Bangladesh Armed Forces Med J Vol 57 No (1) June 2024, pp 8-13